Wokół dyskusji o kondycji polskiego języka literackiego w XVII wieku - Motyl, Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2009)
The article constitutes a compilation and recapitulation of the researchers’ opinions on the condition of the 17th-century Polish literary language. In the beginning of the 20th century, the linguists such as Aleksander Brűckner, Tadeusz Lehr-Spławiński or Zenon Klemensiewicz had a negative opinion on the 17th-century Polish language. In their works they mainly focused on external aspects of the language and pronounced the 17th century as the time of its decline. This attitude altered diametrically under the influence of the studies conducted by Irena Bajerowa. She took a closer look at the structure of the 17th-century Polish and found out that the language was at that time subject to a continuous and uninterrupted development. The works of subsequent linguists confirmed and elaborated Bajerowa’s conclusions. This thesis is also supported by the processes which began, lasted and ended in the 17th century. Among others, the processes include: the demorphologization of grammatical gender in the dative, locative and instrumental cases of the plural number, the separation of masculine category, the disappearance of dual number, the withdrawal of slanting vowels from the language and the formation of a new form of imperative mood of verbs. These processes show numerous attempts at introducing simplifications, regularities and improvements of the system and, as such, they are the manifestation of the permanent and undisturbed evolution of the 17th-century Polish language.